The Need for Testing—The Exercise Challenge Test to Disentangle Causes of Childhood Exertional Dyspnea - Hengeveld, Vera S.; van der Kamp, Mattiènne R.; Thio, Boony J.; Brannan, John D. (Frontiers in Pediatrics, 2022)
Exertional dyspnea is a common symptom in childhood which can induce avoidance of physical activity, aggravating the original symptom. Common causes of exertional dyspnea are exercise induced bronchoconstriction (EIB), dysfunctional breathing, physical deconditioning and the sensation of dyspnea when reaching the physiological limit. These causes frequently coexist, trigger one another and have overlapping symptoms, which can impede diagnoses and treatment. In the majority of children with exertional dyspnea, EIB is not the cause of symptoms, and in asthmatic children it is often not the only cause. An exercise challenge test (ECT) is a highly specific tool to diagnose EIB and asthma in children. Sensitivity can be increased by simulating real-life environmental circumstances where symptoms occur, such as environmental factors and exercise modality. An ECT reflects daily life symptoms and impairment, and can in an enjoyable way disentangle common causes of exertional dyspnea.